Spark of Life: A Novel of Resistance - Erich Maria Remarque (New York Random House Trade Paperbacks, 2014)
509 is a political prisoner in a German concentration camp. For ten years, he has persevered in the most hellish conditions. Deathly weak, he still has his wits about him and he senses that the end of the war is near. If he and the other living corpses in his barracks can hold on for liberation--or force their own--then their suffering will not have been in vain. Now the SS who run the camp are ratcheting up the terror. But their expectations are jaded and their defenses are down. It is possible that the courageous, yet terribly weak prisoners have just enough left in them to resist. And if they die fighting, they will die on their own terms, cheating the Nazis out of their devil's contract.
Keywords: Classics; Fiction; Historical fiction; War fiction